Prospective Memory in Simulated Air Traffic Control: The Impact of Interruptions and Delays - Wilson, Micah (2019)
An invited presentation delivered in reception of an APA (Division 3) Early Career Award 2018. The presentation was part of Cutting Edge Contributions to Experimental and Cognitive Psychology, Division 3.